Optimizing the molecular diagnosis of CDKL5 gene–related epileptic encephalopathy in boys. Issue 11 (29th September 2014) - Mei, Davide; Darra, Francesca; Barba, Carmen; Marini, Carla; Fontana, Elena; Chiti, Laura; Parrini, Elena; Dalla Bernardina, Bernardo; Guerrini, Renzo
Summary Objective Mutations involving the cyclin‐dependent kinase‐like 5 (CDKL5) gene cause an early onset epileptic encephalopathy (EE) with severe neurologic impairment and a skewed 12:1 female‐to‐male ratio. To date, 18 mutations have been described in boys. We analyzed our cohort of boys with early onset EE to assess the diagnostic yield of our molecular approach. Methods We studied 74 boys who presented early onset severe seizures, including infantile spasms and developmental delay, in the setting of EE, using Sanger sequencing, next‐generation sequencing (NGS) and multiplex ligation‐dependent probe amplification (MLPA). Results We identified alterations involving CDKL5 in four boys (5.4%) using NGS in one and MLPA in three. Three of four mutations were indicative of somatic mosaicism. Significance CDKL5 gene mutations accounted for 5.4% of boys with early onset EE. Somatic mosaic mutations might be even more represented than germline mutations, probably because their less deleterious effect enhances viability of the male embryo. The molecular approach used for CDKL5 screening remarkably influences the diagnostic yield in boys. Diagnosis is optimized by Sanger sequencing combined with array‐based methods or MLPA; alternatively, NGS targeted resequencing designed to also detect copy number alterations, may be performed.